Analisis Penerapan Standar Deviasi Dalam Penentuan Persediaan Pengaman Pada Ud Mirama Kota Gorontalo. - Sasmita R. Setiawan (Universitas Gorontalo, 2018)
Currently all companies are looking for opportunities in the openness of international markets or global markets. Companies that can enter this global market are companies that have comparative and competitive advantages. It is necessary to make an important decision concerning the level or quantity of production for the manufacturing company, the determination of the amount or stock of merchandise for the trading company as well as the level of service production for the service company. One important aspect that needs proper management is the supply problem. One of the local companies that became the focus or object of research in this writing is UD. Mirama located in Gorontalo Province, especially the city of Gorontalo which sells AC electronic goods and TV. just like any other trading company the company is also having trouble determining the amount of merchandise inventory. Because often companies have difficulty in the amount of safety stock that must be prepared at the time of booking so that companies can anticipate the number of fluctuating demand. With this problem it is necessary to apply a method used as corporate guidance to overcome the problem of inventory. The method that will try to use is standard deviation method in determining the amount of safety stock. This method is applied to see how the most optimal security inventory, which is the most economical, in the sense that not too much which means waste or additional costs that are not necessary or not too little which means there is still danger of running out of inventory. By using model of qualitative and quantitative analysis, the result of research analysis from the research object is the application of standard deviation method can be determined how much the safety stock will be held by the company and can cover the occurrence of stock out when demand increase or fluctuation in demand.